Daya Predasi Ikan Lemon (Labidochromis caeruleus) dan Ikan Kapiat (Barbonymus schwanenfeldii) Terhadap Larva Nyamuk Aedes aegypti - Nathania Disa Ariesta Andriani; Hebert Adrianto; Arief Gunawan Darmanto (Loka Litbang Kesehatan Pangandaran, 2021)
Dengue hemorrhagic fever (DHF) is a vector-borne disease that still happens every year in Indonesia. This disease is caused by the dengue virus and transmitted by the Aedes aegypti as its vector. One of the biological vector controls that can be implemented is using fish as a predator of mosquito larvae, such as using Electric Yellow Cichlid fish (Labidochromis caeruleus) and Tinfoil Barb fish (Barbonymus schwanenfeldii). This study aimed to determine the difference in predation capacities of Electric Yellow Cichlid and Tinfoil Barb on Ae. aegypti larvae. This research is quasiexperimental with a completely randomized design (CRD) with Post Test Only research design. One aquarium with three liters of water containing one fish is given 25 Ae. aegypti larvae. Testing of each fish species is carried out in five replications. Fish predation was observed every 30 seconds until all larvae were eaten. The result showed that Electric Yellow Cichlid could prey on 25 larvae in an averagetime of 5.7 minutes, while Tinfoil Barb spent 11.6 minutes. The results of the Friedman test showed that there was a significant time difference in preying time of Electric Yellow Cichlid and Tinfoil Barb. It’s concluded that Electric Yellow Cichlid was more effective as an Ae. aegypti larvae predator.